Development of a LAMP method for detecting F129L mutant in azoxystrobin-resistant Pyricularia oryzae. Issue 1 (January 2022) - Li, Changle; Wang, Kai; Zhang, Huazhong; Yang, Di; Deng, Yunyan; Wang, Yingzi; Qi, Zhiqiu
Abstract: Azoxystrobin has been widely used since 1996 to control rice blast caused by Pyricularia oryzae . Azoxystrobin resistance related to mutations at the P. oryzae target protein (F129L of Cytb) has been reported worldwide. To quickly identify and detect resistant strains in the field, this research established a rapid loop-mediated isothermal amplification (LAMP) detection system for the F129L mutation. The system could detect the P. oryzae F129L (TTC-TTA) mutation at 62 °C within 60 min, with a detection limit of 100 fg/μL, which is 10 times higher than for conventional PCR. The method had high specificity and repeatability and could detect the F129L (TTC-TTA) mutation in plant tissues within 3 h. The LAMP method established in this study will be useful to detect azoxystrobin-resistant P. oryzae F129L mutant strains and generate significant data for the management of resistant P. oryzae isolates.